Correlation between major depressive disorder and circulating natural killer cells - Majidi-Zolbanin, Saeedeh; Farnam, Alireza; Nourazar, Seyyed Gholamreza; Movasaghpour, Aliakbar; Ghojazadeh, Morteza; Jafari, Reza; Majidi, Jafar (Archives of Medical Laboratory Sciences, 2019)
Background: Major depressive disorder is a mental disorder characterized by a pervasive and persistent low mood that is accompanied by low self-esteem and loss of interest or pleasure in normally enjoyable activities. Depression is associated with multiple immunological disorders. Aim of the present study was to determine correlation between percentage of circulating NK cells and major depressive disorder. Materials and Methods: Patients older than 18 years with the desire to participate were enrolled in this study. For depression evaluation, we used the Hamilton Depression Rating Scale and for determination of percentage of NK cells in peripheral blood, flow cytometry method was used. Results: Our results showed that in patients with major depressive disorder, numbers of circulating NK cells have significantly reduced. Conclusion: According to our findings, depression is associated with “immune suppression”. NK cells are important in early phase of immunological surveillance versus viral infections and tumors. Indeed, depressive patients are susceptible to cancers and infections.